Beyond Motivation: Multifactorial Determinants of Student Achievement in Cambodian Higher Education - Chat Pound (jfpublisher, 2026)
This study investigates factors contributing to academic achievement among undergraduate students in five higher education institutions in Phnom Penh, Cambodia. Employing a sequential explanatory mixed-methods design, the research collected quantitative data from 399 students through structured surveys and qualitative insights through semi-structured interviews with students, lecturers, and administrators. Multiple regression analyses revealed that personal factors explained 53.9 percent of variance in academic achievement, with motivation emerging as the strongest predictor (β = 0.312, p < 0.001), followed by time management (β = 0.281, p = 0.001) and self-efficacy (β = 0.255, p = 0.002). School climate and social factors accounted for 48.9 percent of variance, with teacher-student relationships (β = 0.286, p < 0.001) and peer support (β = 0.234, p = 0.002) demonstrating significant influence. Economic factors explained 46.4 percent of variance, with family income (β = 0.322, p < 0.001) and access to learning resources (β = 0.286, p < 0.001) constituting primary predictors. Environmental and ecosystem factors, particularly technology and internet access (β = 0.297, p < 0.001), accounted for 42.7 percent of variance. Students in private universities demonstrated moderately higher achievement than public university students (p = 0.014), while no significant gender differences emerged (p = 0.407). The findings extend existing theoretical frameworks by integrating contemporary factors including digital learning, technology integration, and psychosocial well-being. Recommended strategies encompass enhanced scholarships, strengthened lecturer-student relationships, expanded digital infrastructure, increased student participation in decision-making, and multi-stakeholder collaboration aligned with Cambodia's Vision 2050 and national education priorities.